Intra-Hospital Committee for Donation of Organs and Tissues for Transplant: ethical issues - Josiane Cappellaro; Rosemary Silva da Silveira; Valéria Lerch Lunardi; Lisiane Van Ommeren Corrêa; Marina Landarin Sanchez; Isabela Saioron (Universidade Federal do Ceará, 2015)
The objective of this study was to demonstrate ethical aspects involved in the donation, collection and transplantation of organs and tissues through the experiences of workers in an intra-hospital committee for donation of organs and tissues for transplant. Exploratory qualitative research developed with eleven health workers. Data collection was performed at a university hospital in Pelotas, RS, Brazil, in the period of January-March 2010, through interviews. Data analysis resulted in the following categories: understanding of brain death diagnosis as an ethical issue; and, ethical issues experienced by workers in the relationship established with the family. It was concluded that such situations instigate workers to reflect on their attitudes, values, and their role as a health team member and protector of lives.